Analysis of Factors That Influence Taxpayer Compliance With Risk Preferences as a Moderating Variable - Retno Dwi Asri; Ceacilia Srimindarti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Taxes are state funds or income obtained from people or entities with a compelling nature in accordance with applicable laws. The aim of this research is to test and prove the influence of tax understanding, taxpayer awareness and tax sanctions on taxpayer compliance and risk preferences in moderating tax understanding, awareness and sanctions. The theory used in this research is attribution theory. This research uses primary data with quantitative methods through questionnaires and uses purposive sampling techniques with a sample of 231 land and building tax payers in Ngawi Regency. The data was then analyzed using multiple linear regression analysis using SPSS version 23. The results of this research show that tax understanding does not have a significant effect, while taxpayer awareness and tax sanctions have a significant effect. Risk preferences cannot moderate the relationship between tax understanding and taxpayer compliance, but risk preferences can moderate the relationship between awareness and tax sanctions on taxpayer compliance. The research results show that taxpayer awareness and tax sanctions will increase tax revenue if taxpayers are aware of paying taxes, and there are tax sanctions for violators.